The UK's contribution to cancer control in low-income and middle-income countries. Issue 9 (September 2021) - Stanway, Susannah; Lodge, Mark; Sullivan, Richard; Diprose, Kim; Young, Annie M; Crisp, Nigel; Lewis, Philippa; Eden, Tim; Aggarwal, Ajay; Nadin, Amanda; Chinegwundoh, Frank; Sirohi, Bhawna; et al.
Summary: Cancer mortality rates in low-income and middle-income countries (LMICs) are unacceptably high, requiring both collaborative global effort and in-country solutions. Experience has shown that working together in policy, clinical practice, education, training, and research leads to bidirectional benefit for LMICs and high-income countries. For over 60 years, the UK National Health Service has benefited from recruitment from LMICs, providing the UK with a rich diaspora of trained health-care professionals with links to LMICs. A grassroots drive to engage with partners in LMICs within the UK has grown from the National Health Service, UK academia, and other organisations. This drive has generated a model that rests on two structures: London Global Cancer Week and the UK Global Cancer Network, providing a high-value foundation for international discussion and collaboration. Starting with a historical perspective, this Series paper describes the UK landscape and offers a potential plan for the future UK's contribution to global cancer control. We also discuss the opportunities and challenges facing UK partnerships with LMICs in cancer control. The UK should harness the skills, insights, and political will from all partners to make real progress.